Decadal Change in the Population of Dendrogyra cylindrus (Scleractinia: Meandrinidae) in Old Providence and St. Catalina Islands, Colombian Caribbean - Bernal-Sotelo, Katherine; Acosta, Alberto; Cortés, Jorge (Frontiers in Marine Science, 2019)
The IUCN considers the stony coral Dendrogyra cylindrus as vulnerable. However, there is insufficient information on its population structure and dynamics, conservation status, or extinction risk and population decreases have been inferred from observations of habitat degradation. In 2002 and 2012, surveys using manta tows, circular plots and satellite images were performed in Old Providence and Santa Catalina Islands (Seaflower Biosphere Reserve) to determine changes in the condition and structure of a local population of D. cylindrus and its habitat. Size-frequency histograms were asymmetric and leptokurtic, showing positive distribution induced by colony fragmentation, which is indicative of reef degradation. Signs of degradation were more evident in 2012, when partial mortality of living tissue in the parent colony yielded 96.6% of the asexually produced fragments. Most of the fragments were from larger colonies (≥115 cm), which exhibited the highest partial and total mortality (>50%). Three of the four benthic habitats used by the species in 2002 were seen in 2012, but with reduced areas. The results suggest that the reduction of living tissue, the dominance of colonies produced asexually, and reduced size of fragments limit population growth and species viability in an unfavorable and changing habitat within this marine protected area (MPA) of the southwestern Caribbean. In the west of the reef complex of Old Providence, a synergy of multiple stressors could cause the habitat degradation and the fragmentation of colonies, limiting the potential recovery of the species and therefore the ability to create a healthy, genetically diverse and resilient population. Thus, these stressors must be minimized to prevent local extinction. Monitoring the population trends and recording sexual recruitment continues to be vital to understand the larvae’s habitat selection and determine whether these habitats are suitable for the survival of coral recruits. Other stressors to be monitored include anchor damage, diseases and bleaching. We recommend the MPA management program to include specific plans of conservation, recovery and restoration for coral reef builders species like D. cylindrus.